KUALITAS REMOTE AUDIT: DITINJAU DARI SKEPTISISME PROFESIONAL AUDITOR, KOMPETENSI, DAN RISIKO AUDIT - Lovita Alasri, (2022)
This study describes the quality of "remote auditing" as the process by which the auditor interacts with the auditee and collects evidence through electronic means regardless of the physical location of the auditor or auditee. Remote audit promises a positive future with communication technology that continues to evolve. This study was conducted to determine the effect of the relationship between Professional Skepticism, Competence, and Audit Risk on Remote Audit Quality. The survey was conducted at the Public Accounting Firm (KAP) in the South Jakarta area. 88 auditors as research samples taken by purposive sampling method. This study collects primary data by distributing questionnaires through physical observation and google form. This data is processed using SmartPLS. The results showed that Professional Skepticism had a effect on the quality of remote audits. Meanwhile, Competency and Audit Risk have no influence on the quality of remote audit. Keywords: Professional Skepticism, Competence, Audit Risk and Remote Audit